Short- and long-term direct and indirect costs of illness after ostomy creation – a Swedish nationwide registry study - Eva Carlsson; Annabelle Forsmark; Catarina Sternhufvud; Gina Scheffel; Frederikke B. Andersen; Eva I Persson (BMC Health Services Research, 2023)
Abstract Background Despite advance in care of people with an ostomy, related complications remain prevalent. The objective of this study was to examine short- and long-term healthcare resource utilization and associated costs after ostomy creation. Methods This observational study was based on retrospectively collected data from national and regional Swedish registries. The population consisted of people living in Sweden, who had an ostomy created. The earliest index date was 1 January 2006, and people were followed for ten years, until death, reversal of temporary ostomy, termination of purchases of ostomy products, or end of study, which was 31 December 2019. Each person with an ostomy was matched with two controls from the general population based on age, gender, and region. Results In total, 40,988 persons were included: 19,645 with colostomy, 16,408 with ileostomy, and 4,935 with urostomy. The underlying diseases for colostomy and ileostomy creations were primarily bowel cancer, 50.0% and 55.8% respectively, and additionally inflammatory bowel disease for 20.6% of ileostomies. The underlying cause for urostomy creation was mainly bladder cancer (85.0%). In the first year after ostomy creation (excl. index admission), the total mean healthcare cost was 329,200 SEK per person with colostomy, 330,800 SEK for ileostomy, and 254,100 SEK for urostomy (100 SEK was equivalent to 9.58 EUR). Although the annual mean healthcare cost decreased over time, it remained significantly elevated compared to controls, even after 10 years, with hospitalization being the main cost driver. The artificial opening was responsible for 19.3–22.8% of 30-day readmissions after ostomy creation and for 19.7–21.4% of hospitalizations during the entire study period. For the ileostomy group, dehydration was responsible for 13.0% of 30-day readmissions and 4.5% of hospitalization during the study period. Conclusions This study reported a high disease burden for persons with an ostomy. This had a substantial impact on the healthcare cost for at least ten years after ostomy creation. Working ability seemed to be negatively impacted, indicated by increased cost of sickness absence and early retirement. This calls for improved management and support of ostomy care for the benefit of the affected persons and for the cost of society.